2013
DOI: 10.1186/1477-7819-11-19
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside-monosialic acid (GM1) prevents oxaliplatin-induced peripheral neurotoxicity in patients with gastrointestinal tumors

Abstract: BackgroundOxaliplatin, an effective antineoplastic agent againstgastrointestinal tumors, can cause severe peripheral neurotoxicity, which seriously limits its clinical application. To date, there are no effective treatments for this complication. Ganglioside-monosialic acid (GM1) has been shown to protect neurons against injuries and degeneration. The aim of this study was to evaluate the effects of GM1 on preventing oxaliplatin-induced neurotoxicity in patients with gastrointestinal tumors.MethodsIn this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 31 publications
0
24
0
2
Order By: Relevance
“…Although the development of the acute inflammatory polyneuropathy Guillain-Barre´ syndrome (GBS) following intravenous ganglioside treatment resulted in the withdrawal of GM1 from European market [ 31 ], this adverse effect was shown to be rare, and the relationship between exogenous gangliosides and GBS remains controversial [ 32 , 33 ]. These drugs are still available and have been extensively prescribed in other markets including China, where a multitude of neurological maladies have been treated with gangliosides in the absence of resultant GBS or other severe adverse events [ 34 – 37 ]. In a trail conducted by Schneider et al ., a 5-year clinical course confirmed the long-term safety of GM1 therapy and suggested favorable efficacy for Parkinson's disease patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the development of the acute inflammatory polyneuropathy Guillain-Barre´ syndrome (GBS) following intravenous ganglioside treatment resulted in the withdrawal of GM1 from European market [ 31 ], this adverse effect was shown to be rare, and the relationship between exogenous gangliosides and GBS remains controversial [ 32 , 33 ]. These drugs are still available and have been extensively prescribed in other markets including China, where a multitude of neurological maladies have been treated with gangliosides in the absence of resultant GBS or other severe adverse events [ 34 – 37 ]. In a trail conducted by Schneider et al ., a 5-year clinical course confirmed the long-term safety of GM1 therapy and suggested favorable efficacy for Parkinson's disease patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, GM1, a kind of glycosphingolipid, was reported to effectively decrease the incidence of cumulative grade 3 oxaliplatin- and taxane-induced neurotoxicity in a non-randomized and retrospective study. However, no effect on acute, cold-induced neurotoxicity was found ( 12 , 13 ). No substantial differences in permanent discontinuation of chemotherapy and effects on survival were noted between GM1 and control.…”
Section: Discussionmentioning
confidence: 98%
“…There is evidence that application of monosialotetrahexosylganglioside (G M1 ) has therapeutic potential, for example in the treatment of acute spinal cord injury 18,19 . In addition, clinical trials demonstrated that G M1 has symptomatic and disease modifying effects on different human neurodegenerative diseases [20][21][22] . Several studies in rodents have demonstrated that the neuroprotective effect of G M1 seems to be dependent on the interaction with .…”
Section: Dogs Share Many Chronic Morbidities With Humans and Thus Repmentioning
confidence: 99%